SEQUELA AND RISKS OF COVID-19 VACCINES - ali , Wasfi Dhahir Abid; Hasan, Mahfoud Falih; Hameed, Semahir S,; shihab, luay abdulwahid (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Billions of people around the world are vaccinated with the COVI19 vaccine. The virus that claimed the lives of millions of people of different races and ages, and the antiviral vaccine is an important means of preventing and protecting against infection for a period of time. Data of the present study which conducted in Basrah city southern of Iraq , showed that male 46% of the vaccinated participants were male more than female ,59% of them between 23 -30 years of age,72% vaccinated with Pfizer and most of them showed symptom for post vaccination after 1-6 day. Fever significantly rise with Pfizer vaccine, post vaccinated complication correlated with persons have chronic diseases , post complications symptom correlate with age and period, ,sex and work are not significant .